AIAA Guidance, Navigation, and Control Conference 2011
DOI: 10.2514/6.2011-6403
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Perching by an Articulated Wing MAV

Abstract: This paper presents an experimental demonstration of perching by a micro aerial vehicle (MAV) equipped with articulated wings. A novel feature of the MAV considered in this paper is that wing dihedral, controlled independently on both wings, is used for yaw stability and control as well as for maintaining the flight path angle. Yaw stability and control are essential for perching in tightly constrained places. The experiments described in this paper were conducted indoors and flight parameters are measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…Prior experiments by the authors [13], [26] demonstrated the feasibility of using the wing dihedral for longitudinal and lateraldirectional flight control and covered the two key elements of perching: control of flight path (γ) with controlled lateraldirectional control, and the pitch up. The theoretical foundations for the aircraft concept were laid in [22] and [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior experiments by the authors [13], [26] demonstrated the feasibility of using the wing dihedral for longitudinal and lateraldirectional flight control and covered the two key elements of perching: control of flight path (γ) with controlled lateraldirectional control, and the pitch up. The theoretical foundations for the aircraft concept were laid in [22] and [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Obradovic and Subbarao [21,22] computed the power requirements for wing morphing under dynamic loading from maneuvers and identified cases under which morphing is more efficient than traditional control mechanisms. Nonflapping aircraft with fixed as well as articulated wings have been used extensively to study the perching maneuver [18,[23][24][25][26][27]52], which is unique to birds. The perching maneuver has the potential to be adapted by bird-scale micro aerial vehicles (MAVs) to significantly improve their portfolio of maneuvering and mission capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the wing dihedral alone provides sufficient yaw control for trim, but also noted that the sign of the yaw control effectiveness changes as a function of the angle of attack and angular rates. Control laws for stabilizing and maneuvering an articulated wing aircraft have been presented in [3,8]. A roll control mechanism was demonstrated by Stanford et al [9] for an aircraft equipped with highly flexible membrane wings.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…The present paper is concerned with the performance and stability during gliding flight, whereas work is currently in progress in parallel for the flapping phase. A separate analysis of the two flight phases would yield a complete picture of the dynamics of flapping flight, its performance capabilities, and limitations, and create a solid foundation for control design [2,3].…”
mentioning
confidence: 99%